2013
DOI: 10.1093/pasj/65.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Beaming Effect in Fermi Blazars

Abstract: The γ-ray loud blazars (flat spectrum radio quasars-FSRQs and BL Lacertae objects-BLs) are very bright in the γ-ray bands, which is perhaps associated with a beaming effect. Therefore, one can expect that the γ-ray luminosity is correlated with the beaming factor. In this paper, we investigated the relation between the radio Doppler factors and the gamma-ray luminosities. Our analysis suggests that the γ-ray luminosity be strongly correlated with the factor of δ R for the whole sample, FSRQs, and BLs. When the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Fan et al (2013aFan et al ( , 2014 also calculated the γ-ray Doppler factor for this source with adopting the data from 2FGL and obtained 5.99 and 5.62, respectively, both by setting T= 1 d. Our estimation here is higher than the results from Fan et al (2013b) or Fan et al (2014), since some input parameters for calculation are quite different from there, F 1 keV = 4.338 µJy, E γ = 3.13 GeV, and α X = 0.84 are adopted. Fan et al (2013b) and Fan et al (2014) both reported E γ = 3.54 which are similar with this paper but quite low F 1 keV were used, 1.340 µJy and 0.961 µJy presented in Fan et al (2013b) and Fan et al (2014), respectively, and thus led their low estimation of δ γ . From constraining the brightness temperature, Liodakis et al (2018) found the Doppler factor of 11.64 for 3C 279, this value is lower than the average value of their sample.…”
Section: More Implicationsmentioning
confidence: 71%
See 3 more Smart Citations
“…Fan et al (2013aFan et al ( , 2014 also calculated the γ-ray Doppler factor for this source with adopting the data from 2FGL and obtained 5.99 and 5.62, respectively, both by setting T= 1 d. Our estimation here is higher than the results from Fan et al (2013b) or Fan et al (2014), since some input parameters for calculation are quite different from there, F 1 keV = 4.338 µJy, E γ = 3.13 GeV, and α X = 0.84 are adopted. Fan et al (2013b) and Fan et al (2014) both reported E γ = 3.54 which are similar with this paper but quite low F 1 keV were used, 1.340 µJy and 0.961 µJy presented in Fan et al (2013b) and Fan et al (2014), respectively, and thus led their low estimation of δ γ . From constraining the brightness temperature, Liodakis et al (2018) found the Doppler factor of 11.64 for 3C 279, this value is lower than the average value of their sample.…”
Section: More Implicationsmentioning
confidence: 71%
“…Pei et al (2020b) analysed a larger sample of 4 388 AGNs with available log R, 584 are Fermi/LAT-detected blazars from 4FGL, and obtained that the log R for Fermi blazars is higher than that for non-Fermidetected blazars. This is the evidence that the γ-ray emission is strongly beamed (Ghisellini et al 1993;Dondi & Ghisellini 1995;Fan et al 2013b;Pei et al 2016).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…For two variable data sets, , ( = 1, ), we use the linear fitting to analyze their correlations, = ( ± Δ ) + ( 0 ± Δ 0 ), where k is the slope, 0 is the intersection, is the Student's t probability, and n is the number of points in the data set. The Pearson's correlation coefficient r is expressed as [32][33][34]…”
Section: The Relations Between the Spectral Indices And Flux Densitiesmentioning
confidence: 99%